Effect of fat on measurement of bone mineral density - Javed, F. (2009)
OBJECTIVE: To determine if increasing fatness interferes with the measurement of fat and bone mineral density (BMD) by dual-energy X-ray absorptiometry (Lunar iDXA). METHODS: We performed measurements of BMD and fat on a section of a beef femur defatted by prolonged boiling in detergent, completely surrounded by increasing thicknesses of lard. Initially the bone was placed in the marked spine area, overlying a 6L plastic bottle which was placed in the marked trunk area of the iDXA. The plastic bottle was then removed and further measurements were carried out with increasing thicknesses of lard surrounding the bone. Measurements were repeated 4 times. RESULTS: The reported measurement of BMD progressively increased with each increased layer of lard surrounding the bone. All the iDXA BMD measurements were significantly (P<0.01) different from one another. When surrounded by 3 layers of lard the reported BMD was 20.5% greater than the reported BMD when the bone was not surrounded by any lard. The differences between the actual amount of fat measured by chemical analysis and weighing, and the reported measurement of fat by iDXA were significant with all 3 thicknesses of lard (P<0.01); the percentage difference between the fat measured by iDXA and that measured chemically decreased as the number of layers of lard increased. CONCLUSION: We found that iDXA overestimated fat by up to 11.1%. The percentage overestimation of fat diminished as the amount of fat increased. BMD was overestimated by 20.5% when surrounded by 3 layers of fat compared to when there was no surrounding fat. In contrast to fat, the percentage overestimation of BMD increased as increasing amounts of fat surrounding the bone Using earlier generation DXAs, others have reported that measurements were ± 20–50% inaccurate and differed according to the configuration of the phantoms. The measurement of BMD and fat is the main clinical purpose of iDXA; the present experiment has shown that there are substantial inaccuracies in the measurement of BMD and fat. It is not known how these inaccuracies compare with those of earlier generations of DXA machines.